Impact of Second Arterial Conduit on Outcomes Following Coronary Bypass Grafting - Aboul-Hassan, Sleiman Sebastian; Marczak, Jakub; Stankowski, Tomasz; Moskal, Lukasz; Stanislawski, Ryszard; Perek, Bartlomiej; Cichon, Romuald (The Thoracic and Cardiovascular Surgeon, 2022)
Background The aim of this study was to compare short-term outcomes and long-term survival in patients following coronary artery bypass grafting in whom second arterial conduit or saphenous vein was used as well as to find out the most optimal second arterial graft.Methods Between January 2006 and June 2018, 7,857 patients met the inclusion criteria and were divided into two groups: single internal thoracic artery (SITA) + Vein group (n = 7,140) and second arterial conduit group (n = 717), of these 537 patients received right internal thoracic artery (RITA) and 180 patients received radial artery (RA). We obtained 701 propensity-matched pairs for final comparison. Short-term outcomes included: 30-day mortality and major adverse cardiac and cerebral events (MACCE), reoperation for bleeding, and deep sternal wound infection (DSWI). The long-term outcome was all-cause mortality.Results No significant differences were observed between second arterial conduit versus SITA + Vein groups and between RITA versus RA groups in terms of 30-day mortality, 30-day MACCE, reoperation for bleeding, and incidence of DSWI in the matched cohort. The use of second arterial conduit was associated with a significant reduction in long-term mortality by 24% in the matched cohort (hazard ratio [HR]: 0.76; 95% confidence interval [CI]: 0.60–0.96; p = 0.02). RA and RITA as second arterial conduit had comparable long-term mortality (HR: 1.12; 95% CI: 0.69–1.82; p = 0.62).Conclusion The use of second arterial conduit, irrespective of type, is safe and associated with improved long-term survival compared with the second venous aortocoronary graft.
Keywords: coronary bypass grafting; arterial grafting; mortality; outcomes